Hubungan Antara Kepercayaan Diri Dengan Kecemasan Menghadapi Pertandiangan pada Atlet Bulu Tangkis PB Indocafe di Medan - Ririn Sitinjak; Azhar Azis; Faridah Hanum; Babby Hasmayni (Jouska: Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the relationship between self-confidence and anxiety in facing a match. The scale used in this study is the self-confidence scale and the anxiety scale where the subjects in this study are PB Indocafe badminton athletes in Medan, totaling 30 athletes. The data analysis method used in this study is a purposive sampling technique, so the following results can be obtained: the hypothesis proposed in this study reads "There is a negative correlation between self-confidence and anxiety about facing matches in PB Indocafe Medan athletes". This result is evidenced by the following results: 1. The proposed hypothesis is accepted, meaning that there is a negative relationship between self-confidence and anxiety, where rxy = -0.861 with a significant p = 0.000 0.050. 2. The determinant coefficient (r2) of the relationship between the independent variable X and the dependent variable Y is r2 = 0.742. This shows that self-confidence contributes to anxiety by 74.2%. 3. 3. Based on the comparison of the two values (hypothetical and empirical), it can be stated that self-confidence is high because the hypothetical average value of 87.5 is greater than the empirical average value of 81.00, and anxiety is classified as high because the average value the hypothetical 67.5 is smaller than the empirical mean value of 75.54. 3. Based on the comparison of the two values (hypothetical and empirical), it can be stated that self-confidence is high because the hypothetical average value of 87.5 is greater than the empirical average value of 81.00, and anxiety is high because the hypothetical average value is 67 .5 is smaller than the empirical mean value of 75.54. From the results of this study, the proposed hypothesis is accepted.